Directive Speech Acts In The Holy Book Dhammapada Cittavagga Verses - Manggala Wiriya Tantra (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The purpose of this research is to explain how the Dhammapada Scripture Cittavagga Poem uses directive speech acts. The information used in this study came from a variety of literature reviews on speech actions and the Dhammapada text, particularly the 11-verse Cittavagga poem, which has four lines of sacred words in one of its verses. A qualitative approach is the methodology that is employed. According to the study's findings, which were derived from a thorough debate and analysis, the most common types of directed speech are advise (four), reprimands (three), orders (three), invitations (one), and no mention of restriction. It is highly recommended to train, direct, and tame the mind in order to bring happiness. This is the main goal of the directive speech act of advice, which is a very dominant speech act in the linear Cittavagga poem. It emphasizes the importance of maintaining creativity and thoughts that frequently cannot be still and continue to change.